Textural characteristics and organization of composites with fumed silicas and high-molecular weight compounds - V. M. Gun'ko (Хімія, фізика та технологія поверхні)
Various composites with nanosilicas, as well as with other nanooxides, and polymers are of importance from a practical point of view. Detailed textural and morphological characterization, applied here to nanosilicas treated alone and in composites with a set of polymers (poly(vinyl pyrrolidone), poly(vinyl alcohol), poly(ethylene oxide), poly(ethylene glycol), polydimethylsiloxane, and polymethylsiloxane) and proteins (egg albumin, gelatin, and ossein), could be considered as a tool to evaluate the reorganization of hierarchical structures in composites from aggregates of nanoparticles, agglomerates of aggregates, to micro and visible particles. This analysis allows one to elucidate various changes in the porosity, accessible surface area, contributions of pores of different sizes and shapes and pore walls with silica or polymer/protein depending on a set of varied factors. Collected information could be used to forecast possible characteristics and properties of various composites with nanooxides. Among the factors affecting the properties and characteristics of the composites, a type, molecular weight, and content of a polymer and treatment conditions may play an important role. The presence of a large set of the factors makes difficult analysis of the composites using simplified approaches and methods. As a whole, selection of the composition and certain conditions of the composite preparation allows one to control all the textural characteristics of the final materials. For these purposes, the characteristics should be accurately estimated with minimum possible errors using well developed and adequate methods.